Antioxidant activity of Macrolepiota procera wild mushroom submitted to different processing technologies - Fernandes, Ângela (2013)
Mushrooms are very perishable food products and tend to lose quality immediately after harveStr. Drying is the most common method for preserving mushrooms, freezing is becoming increasingly popular and food irradiation has also been suggested by many researchers as a good conservation technique in order to maintain and increase the food shelf life. In the present work, the effects of different processing technologies (freezing, drying and gamma irradiation) on antioxidant activity of the wild mushroom Macrolepiota procera were evaluated. Fruiting bodies were obtained in Trás-os-Montes, in the Northeast of Portugal, in November 2011. The irradiation was performed in experimental equipment with four 60Co sources at 0.6 kGy. The samples were submitted to different processing technologies: freezing (at -20 ºC in a freezer), drying (at 30 ºC in an oven) and gamma irradiation in fresh samples. Antioxidant activity was determined in the methanolic extracts by in vitro assays measuring DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging activity, reducing power, inhibition of β-carotene bleaching and inhibition of lipid peroxidation using thiobarbituric acid reactive substances (TBARS) assay. Total phenolics were also determined by the Folin-Ciocalteu assay. Dried samples gave the highest DPPH scavenging activity (50% at 2.7 mg/mL), β-carotene bleaching inhibition (50% at 1.10 mg/mL) and the highest phenolic content (19.2 mg GAE/g methanolic extract). Frozen and irradiated samples presented the highest reducing power (0.5 absorbance at 1.27 mg/mL) and TBARS formation inhibition (50% at 0.78 mg/mL), respectively. The applied processing technologies affected favourably the antioxidant potential of M. procera extracts, particularly dryness for DPPH scavenging activity and β-carotene bleaching inhibition, freezing for reducing power and irradiation for TBARS formation inhibition.